ANTI-DIABETIC CURE PLANTS IN SUNGAI KIJANG PRIDE - Fitria Lestari; Yuli Febrianti; Ivoni Susanti (Postgraduate, University of Mataram, 2023)
Diabetes Mellitus (DM) is a disease caused by a lack of the hormone insulin and generally consumes medication using chemical drugs due to the fast response in lowering blood sugar levels. However, the use of chemical drugs in the long term can have a negative impact on kidney performance. The way to minimize the negative impact is to use plants as medicine with the following considerations, that is: easy to obtain and minimal side effects. The tribe in Musi Rawas Utara Regency who still maintains the use of plants as medicine as a hereditary inheritance from their ancestors, namely the Anak Dalam Sungai Kijang Tribe in Sungai Kijang Village, Rawas Ulu District, so it is important to inform the wider community regarding this matter. The specific objectives of the study were to describe the types of medicinal plants, to describe the parts of the plants used, and to describe the processing methods for medicinal plants that have anti-diabetic potential. This research method focuses on the types, parts used, and ways of processing medicinal plants with potential anti-dibates for the Anak Dalam Sungai Kijang Tribe. Retrieval of data using observation sheets, questionnaires, interviews, and documentation. The data analysis used is descriptive with a qualitative approach. The results showed 14 types, namely Marasi, Plant Risih, Akar Timah, Pasak Bumi, Kratom, Akar Kuning, Sekubung, Mendururat, Kemeran, Lenteman, Passion, Okinawa Spinach, Kerisan, and Gembili. The organs used are stems, leaves, tubers, and roots. The processing method is washed, eaten immediately, cut, boiled, dropped into the eyes, drunk, and cleaned of the skin. Based on these results it can be concluded that nature always provides what is needed and that is the main principle of the Anak Dalam Sungai Kijang Tribe.